The role of thigh muscle and adipose tissue in knee osteoarthritis progression in women: data from the Osteoarthritis Initiative. Issue 9 (September 2018) - Kemnitz, J.; Wirth, W.; Eckstein, F.; Culvenor, A.G.
Summary: Objective: To determine whether loss in thigh muscle strength in women concurrent with knee osteoarthritis progression is associated with reductions of muscle anatomical cross-sectional area (ACSA) or specific-strength (i.e., isometric force÷ACSA), and to explore relationships with local adiposity. Design: Female participants from the Osteoarthritis Initiative with Kellgren–Lawrence grade ≤3, thigh isometric strength measurements, and thigh magnetic resonance images at year-two (Y2) and year-four (Y4) ( n  = 739, age 62 ± 9 years; body mass index measurements (BMI) 28.8 ± 5.9 kg/m 2 ) were grouped into: (1) those with vs without symptomatic progression (≥9 increase in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)-pain [scale: 0–100]); and (2) those with vs without radiographic progression (≥0.7 mm reduction in minimum joint space width). The change in knee extensor and flexor ACSA and specific-strength, and subcutaneous and intermuscular fat (IMF) ACSAs were compared between progressors and non-progressors using analysis of covariance. Results: Symptomatic progression was associated with a significantly greater loss ( p  < 0.001) of knee extensor ACSA (−2.0%, 95%CI− 2.5,  −1.5) compared to those without progression (−0.7%, 95%CI− 1.0,  −0.4), and greater loss ( p  = 0.020) of knee flexor specific-strength (−7.6%, 95%CI− 11.5,  −3.7; vs −2.4%, 95%CI− 4.8, 0.0). Radiographic progression was associated with a significantly greater increase ( p  = 0.023) in IMF (+1.7%, 95%CI -0.1,  +3.6) compared to those without progression (−0.6%, 95%CI −1.6,  +0.3). Conclusion: The significant reduction in thigh muscle strength concurrent with symptomatic progression in women appears to be associated with loss of extensor muscle ACSA and flexor specific-strength. In contrast, radiographic progression appears to be unrelated to muscle properties, but to be associated with local (intermuscular) adiposity gains.